Thermal-solutal-induced bistability of evaporating multicomponent liquid thin films - Yuki Wakata; Feng Wang; Chao Sun; Detlef Lohse (Proceedings of the National Academy of Sciences, 2025)
Volatile multicomponent liquid films show rich dynamics, due to the complex interplay of gradients in temperature and in solute concentrations. Here, we study the evaporation dynamics of a tricomponent liquid film, consisting of water, ethanol, and trans-anethole oil (known as “ouzo”). With the preferential evaporation of ethanol, cellular convective structures are observed both in the thermal patterns and in the nucleated oil droplet patterns. However, the feature sizes of these two patterns can differ, indicating dual instability mechanisms dominated by either temperature or solute concentration. Using numerical simulations, we quantitatively compare the contributions of temperature and solute concentration on the surface tension. Our results reveal that the thermal Marangoni effect predominates at the initial evaporation stage, resulting in cellular patterns in thermal images, while the solutal Marangoni effect gradually becomes dominant. By regulating the transition time of this thermal-solutal-induced bistability and the nucleation time of oil microdroplets in the ternary mixture, the oil droplet patterns can be well controlled. This capability not only enhances our understanding of the evaporation dynamics but also paves the way for precise manipulation of nucleation and deposition processes at larger scales.